2009
DOI: 10.1186/1755-7682-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic medicolegal cases in Upper Egypt

Abstract: Purpose: To describe the pattern of ophthalmic medicolegal cases with emphasis on cases of assault, and to acquaint ophthalmologists with rules pertaining to expert testimony and medical reports. Methods:A retrospective study was carried out to review files of 247 medicolegal cases from Upper Egypt seen by the senior author in 8 years. These were classified categorically and were analyzed from various characteristics and aspects. The scheme for examination of subjects and for formulating the medicolegal report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 4 publications
5
23
1
Order By: Relevance
“…10 Verdicts decided by judgment favored the doctor in most of the malpractice suits, however most of the claims resolved before judgment process in ophthalmology. [3][4][5] In a study, the compensation ratios and amounts were evaluated and it was observed that although cataract surgery was the leading cause for compensation claims, most of the glaucoma cases resulted in payment. 1 In the present study, cataract accounted for 5 out of a total of 9 compensation cases, consistent with the literature; however, we could not access the data about the paid It was stated that many ophthalmology claims could be observed with diabetic claims.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Verdicts decided by judgment favored the doctor in most of the malpractice suits, however most of the claims resolved before judgment process in ophthalmology. [3][4][5] In a study, the compensation ratios and amounts were evaluated and it was observed that although cataract surgery was the leading cause for compensation claims, most of the glaucoma cases resulted in payment. 1 In the present study, cataract accounted for 5 out of a total of 9 compensation cases, consistent with the literature; however, we could not access the data about the paid It was stated that many ophthalmology claims could be observed with diabetic claims.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in surgical procedures could increase these risks. [4][5][6] Research on epidemiology and etiology of malpractice lawsuits has been gaining importance. The risk of an ophthalmologist taken a place in a medical condition involving malpractice claim (being reported for a malpractice claim) arises.6 In addition, every 100 obstetricians/gynecologists had 0.62-0.91 lawsuit per year, while every 100 ophthalmologists had the lowest lawsuits per year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations